TANGGUNG JAWAB PIHAK TRAVEL TERHADAP PENGGUNAAN MOBIL PRIBADI SEBAGAI ANGKUTAN UMUM PADA CV. D.H. ALENA BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Saiful Anwar; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Transportation is a means that many people need since time immemorial in carrying out activities that are manifested in the form of transportation. Thus the carrier produces services for the people in need is very useful to move passengers. The problems studied are about the number of private vehicles used as public transportation and the constraints faced in the effort of responsibility for private vehicles that do not have a license as a public transport in view of Law Number 22 Year 2009 on Traffic and Road Transport As should have been regulated in the law. Data collection is done by field research that is conducting interview to travel party and library research. The collected data is then analyzed in the form of a regular, systematic, and logical sentence. Based on the research, the authors suggest that the existence of private vehicles as public transportation is often found in Pekanbaru-Tembilahan due to the lack of willingness of the owners of transportation to take care of the required route permit as a condition of public transportation. Obstacles such as lack of information and communication to the public about the socialization of Law No. 22 of 2009 on Traffic and Road Transport, especially about public transportation. Keywords: private vehicle, public transportation